Exploiting The Reputation Of Influencers And Their Credibility To Their Followers In The Process Of Marketing Services Through Social Media - Zakhoy, Hayman Shamsadeen Ali; Jameel, Farhad Salim (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2024)
This study aimed to investigate whether spending on influencer marketing through social media platforms has substantially increased in recent years and how this practice affects customers. Through a proposed